Invasive assessment of aortic stenosis in contemporary practice - Brito, João; Raposo, Luís; Teles, Rui Campante (Frontiers in Cardiovascular Medicine, 2022)
The authors review the current role of cardiac catheterization in characterization of aortic stenosis, its main clinical applications, its pitfalls, and its additional value to information provided by echocardiography. Discrepancies that may arise between these two modalities are discussed and further explained. Hemodynamic variables besides transvalvular gradients are described, and emphasis is given to an integrative approach to aortic stenosis assessment, that includes invasive and noninvasive evaluation.